2020
DOI: 10.1111/cdev.13411
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Person‐Centered Examination of Affinity for Aloneness Among Children and Adolescents

Abstract: Affinity for aloneness (AFA; a tendency to enjoy time spent alone) among children and adolescents often has been viewed as negative, even though research on AFA among these age groups is scarce. Moreover, researchers have not accounted for the role that social anxiety (SA) might play in enjoying solitude. The purpose of this two-wave longitudinal study of children (N = 605, 47.76% female, Mage = 9.29 years) and early adolescents (N = 596, 51.51% female, Mage = 12.20 years) was to identify distinct groups based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 47 publications
4
31
0
2
Order By: Relevance
“…It has been suggested that during the adolescent developmental period, intrinsically motivated solitude becomes viewed as increasingly positive and valuable (Coplan et al., 2019). Consistent with this notion, Daly and Willoughby (2020) recently reported that the percentage of participants who were classified as high in affinity for aloneness and low in social anxiety was higher in their subsample of early adolescents than older children. Coplan et al., (2020) also identified a subsample of unsociable adolescents who were characterized by heightened time spend alone and low sociability, but otherwise not reporting evidence of socio‐emotional difficulties.…”
Section: Discussionmentioning
confidence: 70%
“…It has been suggested that during the adolescent developmental period, intrinsically motivated solitude becomes viewed as increasingly positive and valuable (Coplan et al., 2019). Consistent with this notion, Daly and Willoughby (2020) recently reported that the percentage of participants who were classified as high in affinity for aloneness and low in social anxiety was higher in their subsample of early adolescents than older children. Coplan et al., (2020) also identified a subsample of unsociable adolescents who were characterized by heightened time spend alone and low sociability, but otherwise not reporting evidence of socio‐emotional difficulties.…”
Section: Discussionmentioning
confidence: 70%
“…Given the nature of our study, we were unable to include all items and subscales. Previous research, however, has used this shortened 1-factor version of the SASC-R ( Daly and Willoughby, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…What psychosocial adjustment indicators (i.e., friendship quality, self-esteem, perceived stress, depressive symptoms), measured 1 year earlier, predict membership in these groups (Research question 2)? Given the results of Daly and Willoughby (2020), albeit with a younger population, it is expected that the LCA will reveal an affinity for aloneness group that is not socially anxious, a low group that has low scores on both affinity for aloneness and social anxiety, and several groups who vary in affinity for aloneness but importantly also report moderate to high social anxiety. Further, it is expected that negative psychosocial adjustment, measured 1 year earlier, will increase the likelihood of being in the socially anxious groups rather than the affinity for aloneness or low groups.…”
Section: Current Studymentioning
confidence: 99%
“…Prevalence of affinity for aloneness tends to increase from childhood to adolescence (Daly & Willoughby, 2020; Danneel et al., 2018). For example, Daly and Willoughby found that the prevalence of an affinity for aloneness group was lower in a late childhood sample (grades 3–5) than in an early adolescent sample (grades 6–8), and in both samples, the prevalence increased 1 year later.…”
Section: Introductionmentioning
confidence: 99%